ANALISIS POTENSI BENCANA GELOMBANG LAUT EKSTRIM DAN ABRASI PANTAI DI KAWASAN TANJUNG BUNGA DAN PANTAI BAROMBONG MAKASSAR - Nur, Fitrahwati; Herman, Alifia Pratiwi (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Makassar City is a coastal city in Indonesia with a coastline length of 32 km which includes eleven small islands and a total area of 122,370 km or about 1.1% of the area. This is why Makassar City has a unique character as a coastal city. In recent years, coastal areas in various parts of Indonesia have experienced a very alarming decline, according to the report of the Content Study and Management Plan for Coastal Waters and Oceans, Ministry of Regional Development and Regional Development. Makassar City is one of 30 coastal cities in Indonesia. It is estimated that coastal cities in Indonesia can be affected by rising sea levels in coastal areas, among others; Coastal areas are exposed to negative impacts such as sedimentation (deposition), environmental pollution, then changes in the water system due to human activities and building infrastructure on land but also at sea. The Makassar coastal area has experienced a significant decrease in environmental carrying capacity caused by uncontrolled access to building infrastructure and the condition of the earth's surface shape in coastal areas that can cause disasters. If coastal conditions are not repaired/improved and reduced, it will cause damage to coastal environmental areas which also have an impact on the surrounding areas. The development of this coastal area must be managed by developing the concept of disaster reduction. through the right regional system with me